Diagnostic Concordance between Random Upper Arm Circumference and Mid Upper Arm Circumference Measurements among Children Aged 6–59 Months in South Ethiopia: A Community-Based Cross-Sectional Study - Juhar Admama Bamud; Afework Mulugeta Bezabih; Fentaw Wassie Feleke; Getahun Fentaw Mulaw (Journal of Nutrition and Metabolism)
Random upper arm circumference (RUAC) is frequently used for malnutrition screening among children aged 6–59 months. However, inadequate evidence exists regarding its agreement with mid upper arm circumference (MUAC). This study examined diagnostic concordance between RUAC and standard MUAC measurements and tested RUAC’s ability for screening malnutrition among children aged 6–59 months. A cross-sectional study was conducted from April 30 to May 30/2015 in Ethiopia. Data were taken from a sample of 819 children aged 6–59 months with a simple random sampling technique. The data were analyzed using SPSS version 22 software. The kappa agreement level, sensitivity, and specificity were calculated. The receiver operating curve was prepared to determine the optimal cutoff RUAC for the sensitivity and specificity. With National Center for Health Statistics (NCHS) cutoff (12 cm), the performance of RUAC measurements in terms of sensitivity was low (44%). The kappa agreement level between the two measurements was 0.551 (p value < 0.001). With the new WHO cutoff (12.5 cm), however, RUAC was improved in validity (sensitivity 81%), specificity 96.9%, and kappa agreement level (K = 0.807; p<0.001).